Effect of Educational Facilities and Infrastructure in Primary Schools on Students’ Learning Outcomes - Ruhyana, Nugrahana Fitria; Aeni, Ani Nur (Universitas Pendidikan Indonesia, 2019)
This research aims at revealing the effect of educational facilities and infrastructure in primary schools on students’ learning outcomes. This was based on the Education Data Centre (Dapodik – Data Pokok Pendidikan) of 2017/2018 Academic Year stating that high rates of damage to educational facilities and infrastructures, particularly classrooms, and less optimal students’ learning outcomes indicated higher numbers of students who had repeated a grade (failing a grade). This research employed a quantitative method using the logistic regression as the data analysis technique. Dependent variable in this research was learning outcomes, while independent variables were classrooms, teacher toilets, student toilets, libraries, school based-management (SBM), and double shift. The research population were 599 primary schools in Sumedang District based on Dapodik 2017. The results indicated that there was an effect of educational facilities and infrastructure on students’ learning outcomes, namely classrooms, MBS and double shift, while there was no effect of educational facilities and infrastructure on students’ learning outcomes, namely libraries, teacher toilets, and student toilets.